To Share or Not To Share? Academic Incentives May Hamper Public Good - Cesunica E. Ivey (7443440) (2022)
Over the past several years, the advancement of low-cost air quality monitoring technologies has expanded the scope and scale of air quality research and has provided new opportunities for municipalities and community-led organizations to actively monitor air quality in a manner independent of regulatory agencies. Largely scaled up by private manufacturers, low-cost sensor (LCS) accessibility for monitoring criteria pollutants enables access to near-real-time data for individuals and organizations seeking to create or expand public awareness, advocate for improved air quality, support emissions reductions plans, and identify air pollution sources and hot spots. Other Information Published in: Environmental Science & Technology License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1021/acs.est.2c05721